Disintegrative activation of Pd nanoparticles on carbon nanotubes for catalytic phenol hydrogenation - Zhang, L.; Wang, B.; Ding, Y.; Wen, G.; Hamid, Sharifah Bee Abd; Su, D. (Royal Society of Chemistry, 2016)
The strong dependence of catalytic activity and selectivity on the size of nanoparticles has imposed great value on facile methods for tailoring metal nanoparticles (NPs) with uniform dispersion on a heterogeneous support. Here, a simple and effective method for re-activating sintered Pd NPs decorated on carbon supports is demonstrated using HNO3 vapour at mild temperatures in a closed system, without loss in the Pd content. We further reveal that nitrogen oxide play an important role in the re-dispersion of Pd NPs. In a catalytic phenol hydrogenation reaction, the re-dispersed NPs exhibit superior catalytic activity as compared to sintered Pd NPs supported on CNTs.